CARE FOR SELF-DEVELOPMENT IN RELATION TO THE SELF-REGULATION IN THE STUDENTS OF HELPING PROFESSIONS - Mesárošová, Margita (PEOPLE: International Journal of Social Sciences, 2017)
Self-development of young people is an important task as was emphasized by Erikson (1968/1994). The objective of this study is to explore the nature and components of the care for self-development in college students of helping professions, as well as its predictors. Methods: the care for self-development scale (CSD, Mesárošová, 2014), Learning questionnaire (SRQ-L; Williams, Deci, 1996) were completed by a group of 213 college students (50.7 % were medical students, 49.3 % social work students, 81.7 % were female). Results: factor analysis of CSD produced three factors (the care for development in personal, educational, and general areas), which showed significant positive correlations with the components of the self-regulation in learning (the autonomous and controlled regulation). The only autonomous regulation was proved as a predictor of the care for self-development in both groups of students. Conclusion: our research showed the utility of the self-regulation in predicting the care for self-development in college students. We consider our findings the useful contribution to the educational and counseling process in students of helping professions.